Disrupting ROS-protection mechanism allows hydrogen peroxide to accumulate and oxidize Sb(III) to Sb(V) in Pseudomonas stutzeri TS44. Issue 1 (December 2016) - Wang, Dan; Zhu, Fengqiu; Wang, Qian; Rensing, Christopher; Yu, Peng; Gong, Jing; Wang, Gejiao
Abstract Background Microbial antimonite [Sb(III)] oxidation converts toxic Sb(III) into less toxic antimonate [Sb(V)] and plays an important role in the biogeochemical Sb cycle. Currently, little is known about the mechanisms underlying bacterial Sb(III) resistance and oxidation. Results In this study, Tn5 transposon mutagenesis was conducted in the Sb(III)-oxidizing strainPseudomonas stutzeri TS44 to isolate the genes responsible for Sb(III) resistance and oxidation. An insertion mutation intogshA, encoding a glutamate cysteine ligase involved in glutathione biosynthesis, generated a strain calledP. stutzeri TS44-gshA540 . This mutant strain was complemented with a plasmid carryinggshA to generate strainP. stutzeri TS44-gshA-C. The transcription ofgshA, the two superoxide dismutase (SOD)-encoding genessodB andsodC as well as the catalase-encoding genekatE was monitored becausegshA -encoded glutamate cysteine ligase is responsible for the biosynthesis of glutathione (GSH) and involved in the cellular stress defense system as are superoxide dismutase and catalase responsible for the conversion of ROS. In addition, the cellular content of total ROS and in particular H2 O2 was analyzed. Compared to the wild typeP. stutzeri TS44 and TS44-gshA-C, the mutantP. stutzeri TS44-gshA540 had a lower GSH content and exhibited an increased content of total ROS and H2 O2 and increased the Sb(III) oxidation rate. Furthermore, the transcription ofsodB, sodC andkatE was induced by Sb(III). A positive linear correlation was found between the Sb(III) oxidation rate and the H2 O2 content (R 2  = 0.97), indicating that the accumulated H2 O2 is correlated to the increased Sb(III) oxidation rate. Conclusions Based on the results, we propose that a disruption of the pathway involved in ROS-protection allowed H2 O2 to accumulate. In addition to the previously reported enzyme mediated Sb(III) oxidation, the mechanism of bacterial oxidation of Sb(III) to Sb(V) includes a non-enzymatic mediated step using H2 O2 as the oxidant.